A Motor Learning Approach to Reducing Fall-Related Injuries. Issue 5 (3rd September 2021) - Hsieh, Katherine L.; Sosnoff, Jacob J.
Abstract: Falls are the leading cause of injury related death in older adults. In this piece, a motor learning lens is applied to falls, and falls are viewed as three interdependent phases: 1) destabilization, 2) descent, and 3) impact. This review examines how movements can be performed in the descent and impact phases to potentially reduce fall-related injuries. The evidence that movements performed during the descent and impact phases are voluntary motor skills that can be learned by older adults is reviewed. Data from young adult and older adult studies suggest that safe landing strategies can reduce impact force, are voluntary, and are learnable. In conclusion, safe landing strategies may provide a complimentary approach to reduce fall-related injuries.